Chase's space case ebook - Nickelodeon Publishing (PAW Patrol., 2016)
Chase and the rest of Nickelodeon's PAW Patrol have an out-of-this-world adventure when they help a lost alien find his spaceship. Boys and girls ages 4 to 6 will love this leveled reader.Leveled readers feature big type and easy words. Rhymes and rhythmic text paired with picture clues help children decode the story. This book is for children who know the alphabet and are eager to begin reading. This Nickelodeon Read-Along contains audio narration.